Analog integrated circuit design - Carusone, Tony Chan; Johns, David;Martin, Kenneth (Hoboken, New Jersey : Wiley, 2013)
The discussion of professional applications and the use of real-life circuit design examples make this text a useful tool for both undergraduate and graduate students preparing for circuit design on a professional level.
Includes index.
Keywords: Linear integrated circuits -- Design and construction